Ethics in the practice of públic administratión and its form of care in the Colombian official (2014)
This work is projected on ethical behavior concepts of a public official from their work and responsibility to have against the company, as theme studying so important causes and effects of bad habits as to ethics and moral is recognizing the corruptión of the state administratión because this phenomenon, violating the law duty of the securities represented in solidarity, justice, freedom, equality and human dignity.